2005
DOI: 10.2355/isijinternational.45.937
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Zeolite A Using Blast Furnace Slag

Abstract: Alkali hydrothermal synthesis of zeolite A using blast furnace (BF) slag was investigated. The preliminary experiment was conducted in use of synthetic slag consisting of SiO 2 , Al 2 O 3 , and CaO powders, and it was made clear that the most optimum slag compositions to synthesize zeolite A were the molar ratio of Si to Al (Si/Al) of 1 and reduction of CaO content down to 15 mass%, and that hydrothermal treating conditions were the temperature range from 328 to 358 K, NaOH solution of 1 M (ϭmol/L) and the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 11 publications
1
49
0
Order By: Relevance
“…It is concluded that the reason why the heat of water adsorption of the product was greater than the predicted value is that the Si/Al ratio of the synthesized zeolite A is less than that of commercial zeolite A. Further, not only the formation of zeolite A but also that of tobermorite and hydrogarnet, which had a certain heat storage capacity, 6) was detected. This is also one of reasons why the products have greater heats of water adsorption.…”
Section: Relation Between the Heat Of Water Adsorptionmentioning
confidence: 84%
See 3 more Smart Citations
“…It is concluded that the reason why the heat of water adsorption of the product was greater than the predicted value is that the Si/Al ratio of the synthesized zeolite A is less than that of commercial zeolite A. Further, not only the formation of zeolite A but also that of tobermorite and hydrogarnet, which had a certain heat storage capacity, 6) was detected. This is also one of reasons why the products have greater heats of water adsorption.…”
Section: Relation Between the Heat Of Water Adsorptionmentioning
confidence: 84%
“…From the previous study, 6) it was found that the decrease of CaO content in raw material powders in use of BF slag was essentially needed to synthesize zeolite A. Under the optimum conditions, the addition ratio of BF slag has to be controlled less than 30% of the raw materials.…”
Section: Blast Furnace Slagmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrothermal treatments of BF slag have been applied in the production of heat storage material and high strength building material with additives. [1][2][3][4] In addition, the authors have studied the hydrothermal reaction of the slag for preparing functional materials.…”
Section: Introductionmentioning
confidence: 99%